(untitled) (Szociológiai Szemle, 2023)
Social relations are often crucial elements of a large variety of social phenomena that social scientists study. However, the formalisation of a relational approach in sociology is relatively incomplete. In this study we draw up an analytical framework within which the aims of empirical research can be formulated and analysed. Our main point of departure is the notion of dependence, which arises through the evolution of relations among individuals, connects them on the meso-level of inquiry, and results in outcomes at the group level. We show that the social mechanisms that are responsible for the evolution of these interpersonal relations can be empirically operationalized within the right methodological framework. Finally, we introduce a longitudinal project and describe a unique data set that is suited to the examination of a wide range of social phenomena in an educational setting. We do this by clarifying key theoretical and methodological concepts in the hope that more empirical research and data collection will be carried out in a relational framework in which individuals and their interpersonal relations are considered to be similarly important.